Tracking Chinese aid through China customs: Darlings and orphans after the COVID-19 outbreak - Andreas Fuchs; Lennart Kaplan; Krisztina Kis-Katos; Sebastian S. Schmidt; Felix Turbanisch; Feicheng Wang (Kiel Institute for the World Economy (IfW Kiel), 2022)
Since the outbreak of the COVID-19 pandemic, China's mask and vaccine diplomacy have been widely discussed, but the debate relies on a few stylized data points. This article introduces a systematic way to measure China's foreign aid in almost real-time through official customs records of exported aid goods. Our results show significant shifts in China's aid after the outbreak of the COVID-19 pandemic. First, medical aid skyrocketed after the outbreak. It was initially dominated by face masks and other protective equipment and later by vaccines. This came at the expense of non-medical aid, which was 16.3 percent below its pre-pandemic level. Second, China's aid became global, clearly extending beyond the Global South. Third, in the aftermath of the initial outbreak in March 2020, China's aid became less responsive to both recipient need and political friendship, which can be mainly attributed to the rise of aid through non-government sources. However, in the vaccine diplomacy period of 2021, economic needs and political factors have regained their original importance.
Keywords: F35; F59; H12; H84; I15; I18; P33; 330; official development assistance; aid exports; China; COVID-19; mask diplomacy; vaccine diplomacy; Health Silk Road